If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3j = -2j + 6 Reorder the terms: 3j = 6 + -2j Solving 3j = 6 + -2j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '2j' to each side of the equation. 3j + 2j = 6 + -2j + 2j Combine like terms: 3j + 2j = 5j 5j = 6 + -2j + 2j Combine like terms: -2j + 2j = 0 5j = 6 + 0 5j = 6 Divide each side by '5'. j = 1.2 Simplifying j = 1.2
| 2x-xy+y+5=0 | | 9m+8=88 | | -6x+4c-7x=0 | | 4n=10-2 | | -3x-3y=-48 | | 2cos(2x)-sinx=0 | | 2x^2-3x-4(4x+5)= | | 2c=10-3c | | 0=n^2+4n-80 | | 4(n-2)+11=2 | | X3-1/125 | | .6j+3=2j+0.2 | | 0=n^2+4n-89 | | 15y-18=20y+8 | | -3s=7-4s | | 31=y+4 | | a+18=79 | | X-3x+x=-16 | | -3=m+9 | | 3x-7+-3x+7=0 | | 14-3(a+5)=-20 | | 3x-5y=-59 | | 3x-7+-3x-7=0 | | 10.3032y-8.0348=19 | | 4y+12-3=y+3y+9 | | 11x-7+16x-2=180 | | 4x+204=10 | | 10.3032-8.0348=19 | | 21+5c=63 | | 9/10x-3/5=6 | | 2=0.5(3-x) | | 17x+1+16x+8=180 |